Cerebral Salt Wasting Syndrome following Head Injury in a Child Managed Successfully with Fludrocortisone - Nagendra Chaudhary; Santosh Pathak; Murli Manohar Gupta; Nikhil Agrawal (Case Reports in Pediatrics)
Cerebral salt wasting (CSW) syndrome is an important cause of hyponatremia in head injuries apart from syndrome of inappropriate antidiuretic hormone (SIADH). Proper diagnosis and differentiation between these two entities are necessary for management as the treatment is quite opposite in both conditions. Fludrocortisone can help in managing CSW where alone saline infusion does not work. We report a 17-month-old female child with head injury managed successfully with saline infusion and fludrocortisone.